2004
DOI: 10.1111/j.1460-9592.2004.01258.x
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthesia induction in children: a psychological evaluation of the efficiency of parents’ presence

Abstract: Maternal presence, compared with the father's presence, is fundamental in helping to overcome anxiety in a child receiving anaesthesia. If the parents are present during the induction, the addition of premedication does not offer further benefit. Parents themselves judged their presence during the induction of anaesthesia in their child as a positive event. We also found a statistical significant correlation between anxiety of the parents with the level of the stress of the child during induction of anaesthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
53
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 19 publications
5
53
2
2
Order By: Relevance
“…Based on previous research, anxious parents do not benefit anxious children and they actually increase anxiety in calm children during anesthesia induction. [2324] In a study, Kain et al . reported that presence of a calm parent benefits an anxious child during induction of anesthesia and the presence of an overly anxious parent has no benefit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous research, anxious parents do not benefit anxious children and they actually increase anxiety in calm children during anesthesia induction. [2324] In a study, Kain et al . reported that presence of a calm parent benefits an anxious child during induction of anesthesia and the presence of an overly anxious parent has no benefit.…”
Section: Discussionmentioning
confidence: 99%
“…have recently indicated that anxious parents increase the stress of anesthetic induction in children, even those who have been premeditated. [24] It is suggested that parents were allowed to use their own coping strategies during the preoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…This is a stressful period for the patient's family; emotional involvement may affect peoples' behavior and interfere with solid judgement and common sense, with potential risks for the child and the caregivers. (2,3) …”
Section: Introductionmentioning
confidence: 99%
“…Mothers often assume the caregiver role and are therefore more susceptible to stress, emotional strain and apprehension related issues. (2,3) …”
Section: Introductionmentioning
confidence: 99%
“…3 Among the various routes of premedication, intranasal route has come into practice from early nineties. 4,5 It is relatively a quick, painless with a high bioavailability.…”
mentioning
confidence: 99%